2003
DOI: 10.1007/3-540-44842-x_59
|View full text |Cite
|
Sign up to set email alerts
|

Urban Site Modeling from LiDAR

Abstract: Abstract. This paper presents a complete modeling system that extracts complex building structures with irregular shapes and surfaces. Our modeling approach is based on the use of airborne LiDAR which offers a fast and effective way to acquire models for a large urban environment. To verify and refine the reconstructed ragged model, we present a primitive-based model refinement approach that requires minor user assistance. Given the limited user input, the system automatically segments the building boundary, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 4 publications
0
40
0
Order By: Relevance
“…Aerial and ground-based LiDAR data is being used to create virtual cities [25,10,16], terrain models [23], and classify different vegetation types [3]. Typically, these datasets are quite large and require some sort of automatic processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerial and ground-based LiDAR data is being used to create virtual cities [25,10,16], terrain models [23], and classify different vegetation types [3]. Typically, these datasets are quite large and require some sort of automatic processing.…”
Section: Introductionmentioning
confidence: 99%
“…In relatively flat regions which contain few trees this may yield reasonable results, e.g. the USC campus [25]; however in areas which are forested or highly-sloped, labor-intensive manual input and correction is essential with current methods in order to obtain an useful classification.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the evaluation of methods for 3D building reconstruction is a challenging task [1,8,9,27,64]. Nevertheless, there are still some simple indices that can be used for validation, such as the distance of the input points to the 3D model.…”
Section: Performancementioning
confidence: 99%
“…Most of the demand for these urban models is centered around the creation of navigable 3D virtual models of cities [18] [8] [24].…”
Section: Previous Workmentioning
confidence: 99%
“…Kim and Nevatia [13] propose a similar method but instead they use Bayesian networks to combine edge detection information from multiple images to determine probable building walls. You et al [24] models buildings by means of a user-driven combination of primitive roof shapes that are assembled to form complex building models. We prefer to work only from LIDAR data and with as little manual input as possible.…”
Section: Previous Workmentioning
confidence: 99%